The Influence of Trust and Habit on Users’ Intention to Keep Using Facebook Reels for Economic Purposes - Soviana, Rita; Inan, Dedi I.; Juita, Ratna; Indra, Muhamad (Journal of Applied Informatics and Computing, 2025)
Social media now plays a crucial role in supporting economic activities. Facebook Reels, for instance, as a short video feature, offers economic opportunities for its users. However, understanding the factors that encourage continued usage remains limited. This study aims to explore the influence of trust and habit on users’ intention to keep using Facebook Reels for economic purposes (N=174 active users). We integrated the Technology Continuance Theory (TCT) applied Partial Least Squares Structural Equation Modelling (PLS-SEM) for the analysis. The results show that both factors significantly influence continuance intention (R² = 78.7%), although they do not directly affect user attitude. Attitude is influenced only by reciprocal benefits (R² = 62%). These findings indicate that in regions with limited digital infrastructure such as West Papua, the success of digital platforms strongly depends on building user trust and encouraging consistent usage habit. This study offers valuable insights for platform developers and policymakers in designing strategies to help users continue using the platform over time and support the growth of the local digital economy.